2016
DOI: 10.1021/acs.cgd.6b01391
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Out-Of-Plane Lattice Alignment on the OFET Performance of TIPS-PEN Crystal Arrays

Abstract: In organic field-effect transistors (OFETs), the quality of chargetransport pathway, controlled by crystal structures of organic semiconductors (OSCs), strongly affects the performance of the device. To achieve higher charge mobility, solution-processed single-crystal (SPSC) techniques have been used to decrease crystal defects by aligning the crystals of OSCs in the in-plane direction. Nonetheless, through SPSC techniques, whether the crystalline lattices are wellaligned in the out-of-plane direction and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 35 publications
(49 reference statements)
1
30
0
Order By: Relevance
“…2(a) that the twin boundary is along the [100] direction. This conclusion is also supported by evidence from several other groups [37,38].…”
Section: Molecular Packing Geometrysupporting
confidence: 81%
See 1 more Smart Citation
“…2(a) that the twin boundary is along the [100] direction. This conclusion is also supported by evidence from several other groups [37,38].…”
Section: Molecular Packing Geometrysupporting
confidence: 81%
“…Establishing clear structure-property relationships for TIPS-pentacene is challenging, and we have noticed that there are discrepancies and even contradictory results reported in the literature. Several of these issues include: (1) Multiple groups have reported that the twin boundary of TIPS-pentacene twin grains are along [210] directions [27,61], but our previous report [28] and others [37,38] have found that the boundary is along the [100] direction. It is not yet clear whether these differences are a result of different thin film deposition conditions or due to spurious experimental results.…”
Section: Discussionmentioning
confidence: 98%
“…The polycyclic acenes and heteroacenes such as pentacene, S , N ‐heteropentacene (DTPT), dinaphtho[2,3‐b:2′,3′‐f]thieno[3,2‐b]thiophene (DNTT), dibenzothiopheno[6,5‐b:6′,5′‐f]thieno[3,2‐b]thiophene (DBTTT), and [1]benzothieno[3,2‐b][1]benzothiophene (BTBT) have become the benchmark materials in organic field‐effect transistor (OFET) fabrication to deliver high charge mobilities. [ 1–7 ] However, the generally low solubility of these parent compounds limits their processing to vacuum deposition. To adapt to the trend of easy processing using techniques such as solution‐coating, alkyl substituents at various positions of the polycyclic structures are required to render them sufficient solubility and processability.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of these transistors was very stable and highly reproducible in air. These results suggest that the electrical performance of a compound, especially one exhibiting polymorphism, can be improved by changing the crystallization factors to reach the desired molecular packings; this approach provides a novel means of developing new electrical materials …”
Section: Resultsmentioning
confidence: 99%